Orbital Cellulitis and Periorbital Infections (Springer International Publishing, 2018)
This book discusses the evaluation, diagnosis, and treatment of infections of the orbit and periorbital region and is written by experts in the fields of ophthalmology, oculoplastic surgery, otolaryngology, neurosurgery, and radiology. Infections of the orbit can be challenging to diagnose and manage and it is often difficult for practitioners to stay current with the latest testing, medical treatments, and surgical approaches. Furthermore, as more ophthalmologists are joining hospital-based practices or managed care practices, they often feel uncomfortable when asked to manage these types of patients, either independently or in collaboration with other specialists such as ENT and neurosurgery. Even in many hospitals without ophthalmology coverage, where orbital cellulitis is cared for by otolaryngology and neurosurgery, these specialists also need to be current on the changing trends in managing orbital infections. This book fills the need for a single-source reference for practitioners to turn to for comprehensive information regarding the diagnosis and management of orbital cellulitis. Each chapter is in-depth, yet can also serve as a quick reference guide and is an excellent resource for those in training as well as seasoned practitioners.